The utility of bone marrow sampling in the diagnosis and staging of lymphoma in South Africa. (10th February 2018) - Phillips, L.; Opie, J.
Abstract: Introduction: The bone marrow biopsy (BMB) is a diagnostic and staging tool in lymphoma that remains practically useful and relevant in resource‐constrained settings, despite restricted applications in international staging guidelines, which favour less invasive nuclear medicine techniques. Methods: Retrospective laboratory data review of BMBs in adult lymphoma patients from 2005 to 2010 to determine subtypes, rates of bone marrow involvement (BMI), human immunodeficiency virus (HIV) seroprevalence and CD4 counts, trephine length and additional findings. Results: A total of 1215 BMBs reported in lymphoma included 759 newly diagnosed patients, with BMI in 43.6% of non‐Hodgkin lymphoma (NHL) overall, 28.9% of high‐grade B subtypes and 35.7% of Hodgkin lymphoma (HL). HIV seroprevalence was 38.8%, 53.0% and 33.9% in the 3 respective groups. There was a statistical association between BMI and HIV seropositivity in Burkitt lymphoma and HL, and BMI and CD4 count in HIV‐related HL. Over 10% (n = 79) of new lymphoma cases were diagnosed by BMB with ancillary tests. Occasional histological discordance and transformation were reported in NHL. Focal/unilateral BMI was uncommon. Bilateral BMB and biopsy length exceeding 26 mm did not improve BMI detection. Conclusion: In the South African public sector, high HIV prevalence leads to a different lymphoma pathology profile from the developed world. High BMI rates are encountered. Here, and in similar resource‐constrained settings, international lymphoma staging guidelines can be logistically challenging and unaffordable. BMB remains useful in the staging and diagnosis of lymphoma. Unilateral sampling with a processed trephine length of at least 26 mm is recommended.